Determinants of digital innovation in micro and small industries - Martini Martini; Doddy Setiawan; Retno Tanding Suryandari; Rayenda Brahmana; Andi Asrihapsari (Economies, 2023)
Micro and small industries (MSIs) must utilize digital technology if they hope to meet obstacles and endure in a market that is always evolving owing to technological advancements. This study aims to examine the capacity of business factors, marketing factors, constraint factors, credit factors, entrepreneur factors, and firm factors as determinants of digital innovation proxied by internet adoption and internet usage levels (for communication and information, for promotion, for buying and selling, and for fintech). This study uses a sample size of 90,295 MSIs and secondary data from the MSIs survey in 2019. As analytical tools, logit and ordinary least square (OLS) were employed. The findings demonstrate that business factors, marketing factors, constraint factors, credit factors, entrepreneur factors, and MSIs' firm factors are substantial and continuously affect digital innovation, and primarily its influence is as a motivator. These results will hopefully offer insights for the government as consideration regarding policies on how to encourage MSIs' digital innovation, and for MSIs themselves as references when they are about to make digital innovation decisions.
Keywords: 330; digital innovation; business factors; internet adoption; internet usage levels; micro small industries